A joint resilience scheme with interlayer backup resource sharing in IP over WDM networks. - Lei, Lei (IEEE Communications magazine)
The survivability of IP over WDM networks gains importance as network traffic keeps growing. Recovery at the lowest layer is fast and scalable. However, it is usually considered to provide poor network utilization. In this article we propose a resilience scheme based on recovery at the lowest layer in which intralayer and interlayer backup resource sharing is utilized to improve the network utilization. By applying interlayer backup resource sharing, we can totally depend on the reserved backup resources for fiber link failures to guarantee 100 percent recovery of IP router failures. In addition, by applying intralayer backup resource sharing, the network utilization improvement of recovery at the lowest layer is much more significant than at the highest layer. Simulations results show that the proposed scheme can efficiently improve network utilization and be even more capacity-efficient than resilience schemes based on recovery at the highest layer.